The scenario of norovirus contamination in food and food handlers - Tuan Zainazor, C.; Noor Hidayah, M. S.; Chai, L. C.; Tunung, R.; Mohamad Ghazali, Farinazleen; Radu, Son (The Korean Society for Applied Microbiology, 2010)
Recently, many cases related to viral gastroenteritis outbreaks have been reported all over the world. Noroviruses are found to be leading as the major cause of outbreaks of acute gastroenteritis. Patients with the acute gastroenteritis normally found to be positive with norovirus when stools and vomit were analyzed. This paper reviews various activities and previous reports that describe norovirus contaminated in various food matrixes and relationship between food handlers. Lately, a numbers of norovirus outbreaks have been reported which are involved fresh produce (such as vegetables, fruits), shellfish and prepared food. Food produces by infected food handlers may therefore easily contaminated. In addition, food that required much handling and have been eaten without heat treatment gave the high risk for getting foodborne illnesses. The standard method for detection of norovirus has already been available for stool samples. However, only few methods for detection of norovirus in food samples have been developed until now.